Detection of Ciprofloxacin-Resistant Yersinia pestis by Fluorogenic PCR Using the LightCycler - Lindler, Luther E. (American Society for Microbiology, 2001)
We have developed a fluorescence resonance energy transfer (FRET)-based assay to detect ciprofloxacin resistant (Cp(r)) mutants of the biothreat agent Yersinia pestis. We selected spontaneous mutants of the attenuated Y. pestis KIM 5 strain that were resistant to a ciprofloxacin (CIP) concentration of at least 1 μg/ml. DNA sequencing of gyrA encoded by 65 of these mutants revealed that all isolates contained one of four different point mutations within the quinolone resistance-determining region of gyrA. We developed a FRET-based assay that detected all of these mutations by using a single pair of fluorescent probes with sequences complementary to the wild-type Y. pestis gyrA sequence. Melting peak analysis revealed that the probe-PCR product hybrid was less stable when amplification occurred from any of the four mutant templates. This instability resulted in the PCR product obtained from the Cp(r) Y. pestis strains displaying a 4 to 11°C shift in probe melting temperature. Following optimization of the reaction conditions, we were able to detect approximately 10 pg of purified wild-type template DNA or the presence of approximately 4 CFU of wild-type Y. pestis KIM 5 or Cp(r) mutants in crude lysates. Taken together, our results demonstrate the utility of FRET-based assays for detection of Cp(r) mutants of Y. pestis. This method is both sensitive and rapid.